Pendidikan Agama Kristen di Tengah Budaya Cepat dan Instan: Membentuk Iman yang Bertahan dan Mendalam - Yamsi Ariance Natonis; Daud Saleh Luji; I Made Suardana (Indo Publishing, 2026)
The rapid advancement of digital technology has significantly transformed people's lifestyles, giving rise to a fast and instant culture that influences learning patterns, ways of thinking, social interactions, and spiritual development. This phenomenon presents a major challenge for Christian Religious Education (CRE), as faith formation is essentially a lifelong process that requires guidance, reflection, and the continuous internalization of biblical values. This study aims to analyze the role of Christian Religious Education in fostering resilient and profound faith amid a fast-paced and instant culture, while identifying relevant educational strategies to address these challenges. This research employed a qualitative approach using the library research method. Data were collected from reputable national journal articles, scholarly books, conference proceedings, and other relevant academic publications. The data were analyzed using content analysis through data reduction, thematic classification, interpretation, and conclusion drawing. The findings indicate that the fast and instant culture contributes to a decline in reflective engagement with God's Word, increased exposure to unverified theological information, weakened spiritual depth, and reduced participation in faith communities. To address these challenges, Christian Religious Education should implement Christ-centered learning, integrate digital technology wisely, strengthen spiritual disciplines, and promote collaborative partnerships among schools, families, and churches. This study concludes that digital technology should not be viewed as a threat but rather as a valuable medium for strengthening discipleship when utilized according to Christian theological principles. Therefore, Christian Religious Education remains highly relevant in nurturing a generation characterized by Christian values, spiritual maturity, and resilient, deep-rooted faith amid the ongoing dynamics of the digital era.